Development and in-vitro characterization of tiropramide tablets having immediate- and extended release layers - Muhammad Riaz; Liaqat Ali; Saba Javed; Syed Aatif Hussain; Hassan Haider Shah; Khaleeq Anwer (AMMANIF, 2019)
Purpose: The objective of this study was to explore the feasibility of developing of Tiropramide, bilayer tablet using an immediate- and extended-release formulation. Method: After rheological performance of drug-excipients mixture, Tiropramide HCl bilayer tablets were prepared by wet granulation method. FTIR analysis was performed to elucidate the compatibility behavior of drug and excipients. Effect of these varying concentrations of Ethyl Cellulose (EC) and Hydroxy Propyl Methyl Cellulose (HPMC) were observed on the sustained release pattern of the matrices. Dissolution was performed by using 0.1N HCl and phosphate buffer pH 7.2 as medium at 37.0 ±0.5 ºC, while the stirring speed was set at 50RPM. The bilayer tablets were stored under conditions 40±2oC temperature and 75±5% humidity for stability testing. Results: It was observed that as the quantity of polymers (HPMC or EC) increases the sustained release effect also increases. It was obvious from these models that drug release form bilayer tablets followed the zero order model and Higuchi square root model and the drug release mechanism was diffusion and erosion. The polymers-drug combination was compatible in bilayer tablets before and during stability testing. Conclusion: Bilayer tablet of Tiropramide can be developed successfully in which one layer provides immediate release while the other prolongs the drug release.